Application of B-Lines in Lung Ultrasound for Early Diagnosis of Acute Respiratory Distress Syndrome - Shivi .; Priyasharan Lamba; Shashank Bhardwaj (Archives of Anesthesia and Critical Care, 2023)
Background: Bedside lung ultrasound (LUS) is increasingly being used in diagnosing various lung pathologies. Acute respiratory distress syndrome (ARDS), one of such lung pathology, is a major underlying cause of mortality in critically ill patients. Early diagnosis of ARDS can improve the outcome in such patients. The primary objective of this study is to explore application of B-lines in LUS for early detection of developing ARDS in susceptible patients. Methods: This is a prospective cohort study. This study enrolled patients admitted in intensive care unit. Daily clinical evaluation, bedside chest x ray and bedside lung ultrasound done to diagnose ARDS. Mean days of diagnosing ARDS by chest x ray and LUS were compared using t-test. Area under the Receiver Operating Curves Characteristics was calculated with a 95% confidence interval to determine the prognostic value of LUS. Results: Out of a total of 100 participants, 28 patients developed ARDS. Lung ultrasound was found to diagnose ARDS significantly earlier then chest x ray (p=0.001). Conclusion: Results in this study showed that B-line score in patients susceptible to develop ARDS can help in early diagnosis of the same.